2015
DOI: 10.1111/jvec.12166
|View full text |Cite
|
Sign up to set email alerts
|

Natural vertical transmission of dengue viruses in Aedes aegypti in selected sites in Cebu City, Philippines

Abstract: We attempted to determine the vertical transmission of dengue virus (DENV) in Aedes aegypti in selected sites in Cebu City, Philippines. Mosquito sub-adults were collected monthly from households and the field during the wet-dry-wet season from November, 2011 to July, 2012 and were laboratory-reared to adults. Viral RNA extracts in mosquitoes were assayed by hemi-nested RT-PCR. Results showed that 62 (36.26%; n=679) out of 171 mosquito pools (n=2,871) were DENV+. The minimum infection rate (MIR) of DENV ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
3
22
0
3
Order By: Relevance
“…aegypti mosquito samples in rainy season and in 85 pools in dry season. Infected MIR mosquitoes increased from 0 in rainy season to 48.22 per 1000 mosquitoes in the middle of dry season [9]. Similar results were also obtained from a study conducted in southern India in 204 samples of pools of female Ae.…”
Section: Detection Of Dengue Virus In Male and Female Aedes Aegypti Msupporting
confidence: 84%
“…aegypti mosquito samples in rainy season and in 85 pools in dry season. Infected MIR mosquitoes increased from 0 in rainy season to 48.22 per 1000 mosquitoes in the middle of dry season [9]. Similar results were also obtained from a study conducted in southern India in 204 samples of pools of female Ae.…”
Section: Detection Of Dengue Virus In Male and Female Aedes Aegypti Msupporting
confidence: 84%
“…Transovarial transmission of dengue virus was documented in the field, where different serotypes of dengue virus in larvae or male adult mosquitoes were detected in different areas of the world. 14, 15, 16 A series of laboratory studies confirmed that Ae. aegypti and Ae.…”
Section: Introductionmentioning
confidence: 90%
“…aegypti larvae, female and male mosquito and attributes together with seasonal variable into the predicted model in order to enhance the prediction power. This is because female mosquito can transmit dengue viruses through larvae by trans-ovarian transmission [ 12 , 32 , 33 ] and male mosquitoes can transmit the viruses to females via sexual transmission [ 12 , 33 ]. We found that the infected female mosquito together with season are directly correlated to the number of dengue cases and significantly useful for the forecasting model as confirmed by the results shown in Fig.…”
Section: Discussionmentioning
confidence: 99%